Perception of patient in the intraoperative phase about the invisible care of nursing professionals in Surgical Center in a Private Clinic Of Lima - Salvanha Santos, Poliana (2019)
Objective: The aim of the study was to determine the patient's perception in the intraoperative phase about theinvisible care of nursing professionals of Surgery Center in a private clinic in Lima. Methods: Design study wasquantitative and type research was observational, descriptive, prospective and transversal. The study included90 patients who were treated by nurses in a surgical center. Absolute and relative frequencies, mean, standarddeviation and ranges were used in the statistical analysis. Results: It was found a mean age of 33.3 years,83.3% were female and 47.2% said to be its first surgery. The 81.1% of patients had a favorable respectfultreatment, 81.1% perceived a high tranquility, 97.8% perceived high interpersonal relationship, 78.9% perceivedhigh empathy and 95.6% he presented a high security and privacy. Conclusions: In conclusion, most patientsperceived a favorable invisible care in the intraoperative phase, by the nurses of the Surgical Center in 2016 GoodHope Clinic.